La crisi identitaria nazionale nello specchio dell’Altro secondo i pensatori iraniani dei secoli XIX-XX - Nahid Norozi (Dive-In, 2025)
The article gives an overview of the main contemporary Iranian thinkers who reflect on Persian national identity, particularly in relation to Islam and the Western world. They can be divided into three main currents: those who seek a return to the 'glory' of the pre-Islamic imperial past, re-evaluating the monarchical ideology between the 19th and 20th centuries of the last Qājār kings and especially of the two Pahlavī rulers; those who believe that Persian identity is predominantly shaped by Islamic culture, an idea that developed around the Islamic revolution of 1979; and finally a third group that more moderately supports the multilateral aspect of Persian culture and its national identity, an idea that developed particularly after the Islamic revolution. Both extremist and more moderate attitudes, however, share a certain identity crisis mainly due to the urgency of historical instances and contingent realities, which led Iranian thinkers to a kind of self-analysis and close confrontation with the Other (the Arab, the European).